P187 A phase 1 study to assess the safety, tolerability and pharmacokinetic profile of boceprevir and sildenafil when dosed separately and together, in healthy male volunteers. (18th May 2015) - Mora-Peris, Borja; Else, Laura; Goldmeier, David; Mears, Alison; Weston, Rosy; Graham, Cooke; Khoo, Saye; Back, David; Winston, Alan
Abstract : Background/introduction: Boceprevir is a first generation direct-acting antiviral (DAA) licensed for the treatment of hepatitis C infection. Sildenafil is an oral therapy for erectile dysfunction. As boceprevir is a potent inhibitor of CYP3A4, potential pharmacokinetic interactions may occur when co-administered with sildenafil. Aim(s)/objectives: The aim of this study was to assess the pharmacokinetic profile of sildenafil and boceprevir when dosed separately and together in healthy volunteers. Methods: Thirteen male subjects completed the following study procedures: phase 1 (day 0), single dose sildenafil 25 mg was administered; phase 2 (days 1–9), washout period; phase 3 (days 10–15), boceprevir 800 mg three times a day was administered; phase 4 (day 16), boceprevir 800 mg and sildenafil 25 mg were administered. All drugs were administered in a fed-state. Intensive pharmacokinetic sampling was undertaken on days 0, 15 and 16. Differences in pharmacokinetic parameters of sildenafil, N-desmethyl-sildenafil and boceprevir between phase 4 and earlier phases were evaluated by changes of geometric mean ratios (GMR). Results: All drugs were well tolerated with no safety concerns arising. In the presence of boceprevir (phase 4 versus phase 1), sildenafil GMR maximum plasma concentration (Cmax) and area-under-the-concentration-time-curve (AUC24 ) increased by 1.9 fold (95% CI: 1.5–2.4) and 2.7 fold (95% CI: 2.1–3.4), respectively whereas a reduction in N-desmethyl-sildenafil Cmax was observed (GMR 0.5, 95% CI: 0.4–0.7). No significant changes in boceprevir exposure were observed between phases 4 and 3. Discussion/conclusion: Sildenafil exposure is increased in the presence of boceprevir. Dose adjustment of sildenafil is necessary. An initial dose of 25 mg of sildenafil is suggested.